Guide to introduced pest animals of Australia - West, Peter (CSIRO Publishing, 2018)
A practical guide for the identification of introduced pest animals and management information.
Keywords: Pests -- Australia -- Identification.; Vertebrate pests -- Australia.; Vertebrate pests -- Control.; Vertebrate pests -- Economic aspects.; Pests -- Identification.; Animaux et plantes nuisibles -- Identification.; Vertébrés nuisibles -- Australie.; Vertébrés nuisibles -- Lutte contre.; Vertébrés nuisibles -- Aspect économique.; TECHNOLOGY & ENGINEERING -- Agriculture -- General.; Pests; Vertebrate pests; Vertebrate pests -- Control; Australia; Australian; Electronic books.; Field guides